Causal relationship between renewable energy consumption and manufacturing value added: Evidence from Kazakhstan - Ramil Hasanov; Asli Kazimova; Aytakin Mammadova; Rashad Salahov; Laszlo Vasa (Environmental Economics)
The paper investigates the causal interaction between renewable energy consumption and manufacturing value added in Kazakhstan, a relationship of growing importance in the context of sustainable industrial development. The aim of the study is to assess the direction and nature of causality between these variables over the period from 2000 to 2021. To this end, the Toda-Yamamoto Granger causality test is applied, offering robust results regardless of the order of integration of the time series data. The empirical analysis identifies a statistically significant bidirectional causal relationship. Specifically, renewable energy consumption has a significant impact on manufacturing value added (p = 0.003), while manufacturing value added also significantly influences renewable energy consumption (p = 0.006). These findings reveal a reciprocal mechanism in which the expansion of renewable energy supports industrial growth, and industrial development, in turn, enhances renewable energy usage. The results underscore the strategic importance of integrating renewable energy policies with industrial development plans. From a policy perspective, the study provides practical insights into fostering sustainable economic growth by aligning environmental and industrial objectives in Kazakhstan.